Pola Pembinaan Kepercayaan Diri Penyandang Disabilitas Daksa - Ulfa, Rosy Maria; Jauhari, Tontowi; Bahiroh, Siti (BINA' AL-UMMAH, 2020)
This article discusses guidance patterns and programs, supporting and inhibiting factors in increasing the confidence of people with disabilities at the Integrated Rehabilitation Center for Disabilities Persons at Yogyakarta. This research is done by descriptive qualitative approach. The object of research is mainly the coaching pattern used in increasing the confidence of dissabilities persons. The results of the study show that the pattern of coaching used in increasing the confidence of  disabilities persons is democratic family coaching patterns. Coaching is done by providing a service for social and medical rehabilitation,  and vocational guidance as well. It was also found that the confidence of persons with disabilities was still not optimal, due to the their background, limitation in mastering sign language, overindulgence of persons with disabilities,  and lack of experience to interact with the environment.